Zpracování učebního textu odborného předmětu Poradenské služby pro 4. ročník studijního oboru Kosmetické služby - Bohatá, Květoslava (Univerzita Karlova, Pedagogická fakulta, 2018)
Pro svoji diplomovou práci jsem si zvolila téma tvorby učebních textů pro odborný výcvik studijního oboru Kosmetické služby. Absence těchto kurikulárních dokumentů ztěžuje výuku žákům i učitelům odborného výcviku. Pro výuku jsou často používané texty, které si učitelé odborného výcviku sami připravují v rámci příprav na vyučování a žákům je předávají buď formou okopírovaných listů, nebo jim je nadiktují formou zápisků do sešitu. Mojí snahou je připravit co nejucelenější výukový materiál, který by bylo možné v souladu s tematickým plánem používat k výuce a žákům aby mohl sloužit při domácí přípravě a k opakování probraného učiva. V oboru služeb péče o klienta se zavádějí stále nové a nové postupy, nové technologie, výrobky a přípravky k ošetření, možná i z tohoto důvodu by byl pro vydavatele problém s aktualizací těchto učebnic, a proto na trhu s učebnicemi chybějí. KLÍČOVÁ SLOVA Učebnice, funkce učebnice, parametry učebnice, učební text, školní vzdělávací program I have chosen " Process of teaching texts" as the main topic of my diploma thesis. It is a study support and also materials for professional training of the study branch cosmetic services. Lack of these curriculum documents makes hard both for the students and teachers of the professional training. In lessons they use teaching texts which are prepared by the teachers. These texts are copied for the students or the students make notes from these texts to their exercise books. This teaching style is financially demanding for the teachers and students. The students often loose some sheets with the texts and so it is quite difficult for them to continue in their learning. My aim is to prepare complete teaching material according to the study plan which can be used for the education and also as a study material for the students. There are lots of new methods, technologies, products in the field of cosmetics. It would be a problem for the publishers to update the textbooks. Maybe that is the reason that these textbooks are missing at the market. KEYWORDS Textbooks, textbook functions, parameters, teaching materials, textbooks, school educational programme Katedra pedagogiky Pedagogická fakulta Faculty of Education